Experimentações, leitura, projeto - Matilde Maria Magalhães Corrêa (Centro Universitário Salesiano de São Paulo, 2016)
This book deals with the experiences of many teachers with "work projects", a bold new "methodology", which lets you work with multiple languages to the students: music, body, oral and writing, mathematics, among others, in different times and spaces of the Traditional Education with intent, records and evaluations that are theirs. The explicitness of these student experiments carried out on site School, located in Campinas/SP, is based on sociointeractionists theories, and aim transdisciplinary knowledge, teamwork, and self-knowledge, valuing them in learning that leads to autonomy, reflection and social transformation.